Optimization of ORC-Based Micro-CHP Systems: An Experimental and Control-Oriented Study - Santos, Márcio; André, Jorge; Mendes, Ricardo; Ribeiro, José B. (Processes, 2025)
This study presents an experimental and numerical investigation into the performance and control optimization of an Organic Rankine Cycle (ORC)-based micro-combined heat and power (micro-CHP) system. A steady-state, off-design, charge-sensitive model is developed to design a control strategy for an ORC micro-CHP combi-boiler, aiming to efficiently meet real-time domestic hot water demands (up to 40 °C and 35 kW) while generating up to 2 kW of electricity. The system utilizes a natural gas burner to evaporate the working fluid (R245fa), with combustion heat power, volumetric pump speed, and expander speed as control variables. Experimental and numerical evaluations generate steady-state control maps to identify optimal operating regions. A PID-based dynamic control strategy is then developed to stabilize operation during start-ups and user demand variations. The results confirm that the strategy delivers hot water within 1.5 min in simple boiler mode and 3 min in cogeneration mode while improving electricity generation stability and outperforming manual control. The findings demonstrate that integrating steady-state modeling with optimized control enhances the performance, responsiveness, and efficiency of ORC-based micro-CHP systems, making them a viable alternative for residential energy solutions.